ANALISIS PENERAPAN RULE OF REASON DALAM PENEGAKAN HUKUM ATAS PERSEKONGKOLAN BARANG/JASA DI KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT (PUPR) KALIMANTAN TENGAH - Ilham Ilham; Rika Lestari; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research is motivated by the results of decisions in KPPU decisions Number03/KPPU-L/2018, Number 04/KPPU-L/2018, and Number 06/KPPU-L/2018 . Stakeholderemployees appointed to be on the tender implementation committee were involved in theconspiracy to win one of the business actors. The tender committee facilitated collusion withone of the tender participants. The action taken by the tender implementation committee is toorganize and win certain tender participants, namely one of the Reported Parties, by providingexclusive and preferred opportunities and to help organize the Reported Party group to be ableto win the tender by displacing other Reported Parties at the technical level even though thedocuments are complete.This research aims to determine the application of the rule of reason approach and lawenforcement regarding goods/services collusion in the Ministry of Public Works and PublicHousing (PUPR) in Central Kalimantan. The method used is descriptive normative legalresearch using a statutory-regulatory approach to regulations relating to Article 22 of the Anti-Monopoly and Unfair Business Competition Law. This research source uses primary,secondary and tertiary legal materials with data collection techniques based on literature studyand data analysis techniques using the deduction method.The research results obtained are related to the application of the rule of reasonapproach to 3 (three) KPPU decisions, namely Numbers 03/KPPU-L/2018, 04/KPPU-L/2018,and 06/KPPU-L/2018, which are still not perfectly implemented. Furthermore, regarding lawenforcement regarding goods/services collusion that occurred at the Ministry of Public Worksand Public Housing (PUPR) in Central Kalimantan, in this case to the working group as oneof the respondents, the Assembly did not follow the provisions of Article 47 Paragraph (2)Letter F which stipulates there was payment of compensation even though it was legal andproven to fulfill the elements of tender conspiracy as explained in the case above. Even thoughall of the Reported Parties have been legally and convincingly proven in accordance withArticle 22.Keywords : Tender Committe, Conspiracy, Tender